Clinical Case Conference: Strategies for Transferring From Methadone to Buprenorphine. Issue 2 (15th March 2022) - Hill, Duncan; Hayes, Victoria; Demirkol, Apo; Lintzeris, Nicholas
Abstract : The mainstay of treatment for opioid use disorder are medications, methadone (a full opioid agonist), or buprenorphine (a partial opioid agonist), in conjunction with psychosocial interventions. Both treatments are effective but safety, efficacy, and patient preference can lead to a decision to change from one treatment to the other. Transfer from buprenorphine to methadone is not clinically challenging; however, changing from methadone to buprenorphine is more complex. Published reports describe varied approaches to manage this transfer to both minimize patient symptoms associated with withdrawal from methadone and reduce risk of precipitating withdrawal symptoms with introduction of the partial agonist buprenorphine [Lintzeris et al. J Addict Med . 2020; in press]. There is no single approach for methadone to buprenorphine that is superior to others and no approach that is suitable for all case presentations. This case conference describes three different approaches to achieve a successful methadone to buprenorphine transfer and provides commentary on how the case may be managed based on published transfer "strategies."